Kandungan Mikrob Daging Kelelawar yang Diolah sebagai Bahan Pangan Tradisional MICROBIAL CONTENT IN THE PROCESSED MEAT BATS AS TRADITIONAL FOOD - Ransaleleh, Tiltje Andretha; Maheswari, Rarah Ratih Adjie; Sugita, Purwantiningsih; Manalu, Wasmen (Jurnal Veteriner, 2013)
This study was designed to assess the microbial characteristics of bats meat which were cooked askari and rica-rica, and were stored up to 14 days.The study was divided into two stages, the first stage usedthree types of bat meat that were cooked as rica-rica and kari 14 days after being stored in the refrigerator.The second stage used meat of a species of bat that was cooked as rica-rica and kari a few hours afterslaughtering. The result of the meat analysis at the 1st showd that thetotal count of microbials i.e;Staphylococcus aureus, Escherichia coli, coliform, and Salmonella sp from three species of bats that werecooked rica-rica  and  kari  were above the maximum limit of microbial contaminant occording to BSN(2009). The analysed made on the rica-rica showed that bat meat rica-rica stored up to 14 days containedtotal microbial count of 3,1 x 104 - 6,0 x 104Cfu/mL, Staphylococcus aureus 7,7 x 101- 7,6 x 103 Cfu / mL,Escherichia coli and Salmonella sp was negative. The total microbial count  of bat meat kari was  6,8 x 105-9,7 x 105Cfu/mL,  Staphylococcus aureus  was 4,3 x 101-1 x 104 Cfu /mL.  Escherichia  coli <3 / mL, andSalmonella sp was negative. Based on the result abtained, it was concluded that the bat meat rica-ricaand kari which were cooked in a few hours after cutting and stored until 14 days were suitable for humanconsumption.
Keywords: bat meat, kari, rica-rica, microbial count